Overview of the Cause of Death of the Forensic Section of DR M.Djamil Hospital, Padang in 2019 - Mega Miftahul Rizka; Rika Susanti; M Fadil (Journal of Midwifery, 2021)
Backgrounds: Death eventually occurs in all living things. Statistical data of deaths are needed to determine policies, priorities, and development of health programs in order to improve health service provisions.Objectives: This research implemented a retrospective descriptive design. Samples were selected using total sampling technique. Samples were taken from data recorded in the death registration form in RSUP M. Djamil Padang from January to December 2019. Data analysis was carried out univariately.Results: Characteristic of corps in the Forensic Unit of RSUP DR M.Djamil Padang in 2019 was found that more deaths occurred in men (53.9%) and elderly age (> 45 years) groups. The most common causes of death based on the ICD-10 classification were symptoms, signs, and other abnormalities (31.9%), disease of the respiratory system (14%) and the circulatory system (16%). On 125 of 212 corpes with unnatural death (59%), external examinations were performed.Conclusion: The number of death is higher in male and elderly age with the most common cause of death group is symptoms, signs, and other abnormalities.